2018
DOI: 10.1108/cdi-12-2016-0214
|View full text |Cite
|
Sign up to set email alerts
|

Socialization resources theory and newcomers’ work engagement

Abstract: Purpose Although work engagement has become an important topic in management, relatively little attention has been given to newcomers’ work engagement in the socialization literature. The purpose of this paper is to explain how newcomers’ work engagement can fluctuate during the first year of organizational entry and the role of organizational socialization in developing and maintaining high levels of newcomers’ work engagement. Design/methodology/approach A review of the socialization literature indicates t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
137
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(152 citation statements)
references
References 66 publications
10
137
0
5
Order By: Relevance
“…Concerning the relationship between the psychological resources and work engagement (H1), our results support the idea that a good appraisal of “psychological resources linked to the working environment” was a promoting factor in work engagement in terms of dedication, absorption, and vigor. These results are in line with current literature demonstrating that job resources (Bakker et al, 2007), social support (Saks and Gruman, 2018), and autonomy (Heyns and Rothmann, 2018), might positively affect levels of engagement. Contrary to our expectation (H2), the direct effect of work engagement on teaching practices was small and not statistically significant.…”
Section: Discussionsupporting
confidence: 92%
“…Concerning the relationship between the psychological resources and work engagement (H1), our results support the idea that a good appraisal of “psychological resources linked to the working environment” was a promoting factor in work engagement in terms of dedication, absorption, and vigor. These results are in line with current literature demonstrating that job resources (Bakker et al, 2007), social support (Saks and Gruman, 2018), and autonomy (Heyns and Rothmann, 2018), might positively affect levels of engagement. Contrary to our expectation (H2), the direct effect of work engagement on teaching practices was small and not statistically significant.…”
Section: Discussionsupporting
confidence: 92%
“…Female workers are entering the workforce at this age, when menstruation is most likely to be distressing. The primary goal for these workforce newcomers is adaptation—processing new information and challenges, managing stress, creating a positive impression, and building social capital and relationships (e.g., Collins & Stevens, 2002; Saks & Gruman, 2018; Whitely, Dougherty, & Dreher, 1992). Thus, newcomers must learn quickly and build relationships with peers and supervisors; however, the beliefs and experiences of menstruation appear incongruent with such goals (see Figure 1).…”
Section: A Review Of the Three Ms In Organizational Lifementioning
confidence: 99%
“…More recent work found that dual-task performance (i.e., performing a cognitive task at the same time as another task) was not affected across the menstrual cycle (Ni, Hazzard, & Smith, 2018), and Sundström-Poromaa (2018: 349) noted that “the overall conclusion is that the menstrual cycle differences in sexually dimorphic cognitive tasks are small and difficult to replicate.” In fact, only 28.8% of Italian women surveyed agreed that menstruation interfered with work focus (Ferrero et al, 2006). Yet, daily menstrual pain was related to feeling mentally depleted among U.S. women (Motro et al, 2019), which may be particularly problematic for young workers, who are more likely to feel discomfort while menstruating (László & Kopp, 2009) and need their full cognitive capacity to learn and develop new skills (e.g., Saks & Gruman, 2018).…”
Section: A Review Of the Three Ms In Organizational Lifementioning
confidence: 99%
“…Pesquisas sobre socialização e comprometimento organizacional trouxeram grandes contribuições, tanto no sentido de esclarecimento acerca dos construtos, quanto à disponibilização de instrumentos de medida válidos e consistentes (Allen, Eby, Chao, & Bauer, 2017;Moyson, Raapshorst, Groeneveld, & Van de Walle, 2018;Saks & Gruman, 2018). No que se refere à investigação destes fenômenos no contexto das organizações militares ou organizações policiais, as pesquisas (Dick, 2011;Rodrigues & Bastos, 2013;Wortmeyer, 2007) se dedicaram a entendê-los isoladamente, ou seja, concentraram-se em compreender ou os processos de socialização organizacional, ou os de comprometimento, de modo que se observa uma carência de estudos que investiguem a natureza correlacional desses fenômenos nesse contexto organizacional em específico.…”
Section: Introductionunclassified